Ultrathin Gold Microelectrode Array using Polyelectrolyte Multilayers for Flexible and Transparent Electro‐Optical Neural Interfaces. (21st November 2021) - Hong, Woongki; Lee, Jee Woong; Kim, Duhee; Hwang, Yujin; Lee, Junhee; Kim, Junil; Hong, Nari; Kwon, Hyuk‐Jun; Jang, Jae Eun; Punga, Anna Rostedt; Kang, Hongki
Abstract: Electro‐optical neural interface technologies provide great potential and versatility in neuroscience research. High temporal resolution of electrical neural recording and high spatial resolution of optical neural interfacing such as calcium imaging or optogenetics complimentarily benefit the way information is accessed from neuronal networks. To develop a hybrid neural interface platform, it is necessary to build transparent, soft, flexible microelectrode arrays (MEAs) capable of measuring electrical signals without light‐induced artifacts. In this work, flexible and transparent ultrathin (<10 nm) gold MEAs are developed using a biocompatible polyelectrolyte multilayer (PEM) metallic film nucleation‐inducing seed layer. With the polymer seed layer, the thermally evaporated ultrathin gold film shows good conductivity while providing high optical transmittance and excellent mechanical flexibility. In addition, strong electrostatic interaction via the PEM alters the electrode‐electrolyte interfaces, thereby reducing the electrode impedance and baseline noise level. With a simple modification of the fabrication process of the MEA using biocompatible materials, both excellent transmittance, and electrochemical interface characteristics are achieved, which is promising for efficient electro‐optical neural interfaces. Abstract : Ultrathin (<10 nm) gold microelectrode arrays (MEAs) are fabricated using polyelectrolyte multilayer coating as the metallic nucleation‐inducing seed layer for achieving electrical conductivity while being optically transparent. With this simple microfabrication process, the mechanical flexibility and electrochemical properties of the transparent electrodes are significantly improved for efficient electro‐optical neural interfaces. The biocompatibility of the MEAs for neuronal culture is also validated.